NGF and BDNF Alterations by Prenatal Alcohol Exposure - Carito, Valentina; Ceccanti, Mauro; Ferraguti, Giampiero; Coccurello, Roberto; Ciafrè, Stefania; Tirassa, Paola; Fiore, Marco (Current Neuropharmacology, 2019)
Background: It is now widely established that the devastating effects of prenatal alcohol exposure on the embryo and fetus development cause marked cognitive and neurobiological deficits in the newborns. The negative effects of the gestational alcohol use have been well documented and known for some time. However, also the subtle role of alcohol consumption by fathers prior to mating is drawing special attention. Objective: Both paternal and maternal alcohol exposure has been shown to affect the neurotrophins' signalling pathways in the brain and in target organs of ethanol intoxication. Neurotrophins, in particular nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), are molecules playing a pivotal role in the survival, development and function of the peripheral and central nervous systems but also in the pathogenesis of developmental defects caused by alcohol exposure. Methods: New researches from the available literature and experimental data from our laboratory are presented in this review to offer the most recent findings regarding the effects of maternal and paternal prenatal ethanol exposure especially on the neurotrophins' signalling pathways. Results: NGF and BDNF changes play a subtle role in short- and long-lasting effects of alcohol in ethanol target tissues, including neuronal cell death and severe cognitive and physiological deficits in the newborns. Conclusion: The review suggests a possible therapeutic intervention based on the use of specific molecules with antioxidant properties in order to induce a potential prevention of the harmful effects of the paternal and/or maternal alcohol exposure.
Keywords: oxidative stress